Various Types Of Spices Concentration with Inhibition Of The Bacterium Streptococcus Pyogenes - Soesanto Soesanto; Teguh Budiharjo; SY.Didik Widiyanto (Poltekkes Kemenkes Semarang, 2013)
This study is an experimental study using a factorial design with variable influence (independent) is the concentration of 100%, 80%, 60%, 40%, 20%, and the type of spice Powder, turmeric, ginger, turmeric, onion while its impact variable (dependent) is the inhibition of the bacteria Streptococcus pyrogenes marked by a blank zone area.The data was analysis of variance (ANOVA) The concentration of the herb affects the inhibition of the growth of bacterium Streptococcus pyogenes. Inhibition of the greatest concentrations of 100%, and the inhibition of the smallest on the concentration of 20%. Powder is a spice that has the greatest inhibition of the clear zone is measured as 5.53 mm.